Experimental studies of the characteristics of a resonant leader emitter with a single-pass amplifier - Zarudnyi, A.A. (Radiotekhnika, 2024)
The results of experimental studies of the energy and spatial characteristics of the lidar transmitter, built according to the generator-amplifier scheme based on an organic dye with tube pumping, are presented. The choice of a single-pass traveling wave amplifier used in the experiments was determined by preserving the spectral purity of the radiation. When constructing a lidar emitter according to the generator-amplifier scheme under conditions of constant pumping density, the problem arises of choosing the ratio between the length of the active element of the generator and the length of the active medium of the traveling wave amplifier, which would ensure the maximum efficiency of the entire emitter. The main task of the work was the experimental verification of the results of theoretical studies of the narrow-band emitter of the resonant lidar in order to determine the factors affecting the choice of the ratio of the lengths of the active elements of the generator and the amplifier based on the organic dye rhodamine 6Zh with tube pumping with limited total length. The amount of effective radiated energy was used as the main criterion for evaluating the efficiency of the generator-amplifier system. The experimental results confirm the theoretical conclusions that there are optimal ratios of the lengths of the generator and the amplifier, at which the effective radiation energy is maximal. The limiting length of the amplifier and the energy of the emitter built according to the generator-amplifier circuit are limited by the increase in the intensity of the radiation amplified along the active element, as well as the increase in the intensity of the amplified noise.